Mindfulness, crashes, and risky driving behaviors among adolescents and young adults in the United States - Johnathon P. Ehsani; Michelle Duren; Sjaan Koppel; Federico Vaca; Andrew Hellinger; Brydon Grant; Ahmed Sabit; Gayane Yenokyan (Transportation Research Interdisciplinary Perspectives)
Purpose: The purpose of this study was to examine the association between individual-level mindfulness and a range of risky driving behaviors among U.S. adolescents. Methods: We conducted a survey of a nationally representative sample of 16–19-year-olds, recruited from the National Opinion Research Center AmeriSpeak panel, a probability-based sample. Participants completed the Mindful Attention Awareness Scale. Risky driving measures were adapted from the Youth Risk Behavior Survey. Spline regression analysis was performed to identify the threshold where mindfulness scores significantly changed driving behaviors. Results: After adjusting for age, gender, and race, adolescents reporting higher mindfulness scores were significantly less likely to engage on all risky driving behaviors and significantly less likely to have been involved in a crash. Spline regression analysis indicated that a mindfulness score of 75 corresponded to the minimum marginal probability change averaged across the outcomes of interest. Discussion: This paper describes a previously unknown association between mindfulness and risky driving in a vulnerable population which is at higher risk of injury and death from motor vehicle crashes. The strength of the associations across a range of behaviors suggests mindfulness could be a general protective factor for adolescents’ driving behaviors and suggests that mindfulness training may be a promising safety intervention for adolescents. A mindfulness score of 75 could be a potential target for mindfulness training interventions aiming to reduce risky driving behaviors and crashes among teenage drivers.Abbreviations: ADHD, Attention Deficit Hyperactivity Disorder; CI, Confidence Interval; MAAS, Mindful Attention Awareness Scale; NORC, University of Chicago’s National Opinion Research Center; YRBS, Youth Risk Behavior Survey.